Perspektif Gender : Pengaruh Intelligence Quotient Terhadap Pemahaman Mata Kuliah Ekonomi Mikro Islam (Studi Empiris Di Kampus Stebis Igm Palembang) - Melis Melis (An Nisa'a, 2018)
The differences of understanding and point of view on gender and gender equity have become the basis of this study. It exploits the distinction any further particularly in academic community. The focus of study is specifically on the orientation of research theme and the direction of gender study analysis which are written by in undergraduate thesis. The study is successful in identification that gender study themes have been dominated by the contextual study or aplicative-empiric instead of the study of textual or normative-legalistic. Gender study is viewed as the study about women not about gender or the study utilizing gender as tool of analysis. The analysis of women study mostly use descriptive one, it only describes position and role of women, whereas the gender study uses critical analysis, that ilustrate the arguments behind the role and position of women. It could be identified wether the position and role of women are equal or not with men.